Physiologic Osseous Remodeling of the Anterior Wall of the Spinal Canal after Anterior Cervical Corpectomy and Fusion: A Retrospective Observational Study - Ni, Haofei; Mao, Wei; Li, Hailong; Dong, Youhai (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Anterior cervical corpectomy and fusion (ACCF) has been widely used in the treatment of cervical spondylotic myelopathy (CSM), ossification of posterior longitudinal ligament (OPLL), cervical trauma, and other cervical diseases, but few studies have reported the osseous and physiologic remodeling of the anterior wall of the spinal canal following ACCF. In this study, we analyze that remodeling process and its influence on titanium mesh cage (TMC) subsidence.Methods We performed a clinical and radiologic analysis of consecutive patients treated with ACCF. Growth rates (GRs) reflecting the extent of remodeling of the remnants of the resected vertebral bodies were measured. We compared the computed tomography (CT) scans taken immediately and at least 1 year after surgery, and a literature review was conducted.Results In all, 48 patients underwent ACCF at a mean age of 61.5 ± 12.0 years. The median follow-up was 36 months, and 159 CT images were analyzed. The GR values of the remnants of the vertebral bodies on CT images immediately and 1 year after surgery were 0.505 ± 0.077 and 0.650 ± 0.022 (p < 0.001), respectively, and the GR value at ≥4 years was 1. Axial CT scans showed that remodeling starts from the lateral remnants of the resected vertebral bodies, finally reaching the center. When fusion of the vertebral bodies and the titanium cage was complete during the first year after ACCF, osteogenesis and remodeling were initiated in the osseous anterior wall of the spinal canal. The remodeling of the osseous anterior wall of the spinal canal was completed at the fourth year after surgery, without recompressing the spinal cord, as seen on both axial and lateral CT scans. According to the literature review, there was no TMC subsidence at more than 4 years after surgery.Conclusion The anterior wall of the spinal canal undergoes osseous remodeling after ACCF. The process is complete in the fourth year after surgery and prevents TMC subsidence.
Keywords: ACCF; cervical spine; bone reconstruction; osseous fusion; cerebrospinal fluid pulsation